An investigation of the factors affecting ownership and use of bank accounts in Ghana - Aurélie Larquemin (University of Bath, Centre for Development Studies (CDS), 2020)
Enabling everybody to benefit from regulated financial services has become a global policy goal. However, while access to accounts is increasing, use of accounts remains low. This micro-level study considers the transactions and savings components of financial inclusion, and investigates the factors affecting use of regulated savings accounts by individuals in Ghana. It investigates, for the first time on a single country national dataset, the five sets of constraints on use of regulated savings accounts identified by Karlan et al. (2014): transactions costs, information and knowledge gaps, social connections, trust in banks and behavioural biases. It uses logistical regression analysis to assess the role of the five constraints on account use in Ghana using individual level data from a nationally representative sample collected by Finscope in 20101. The results show that, while the constraints considered by Karlen et al. (2014) affect the access to bank accounts, they do not influence the use of these accounts.
Keywords: 330; bank accounts; savings; financial inclusion; access; use; Ghana